Strategies For Developing Thinking For The Professional And Cultural Education Of Future Teachers Using Gender Models - pcadmin, Urishov Shakir Mamataliyevich (Genius Journals, 2025)
This research paper explores strategies for developing thinking that can be used for the professional and cultural education of future teachers, with a particular focus on the use of gender models. The paper highlights the importance of incorporating a gender perspective into teacher education programs. By reviewing current literature on developing thinking, gender studies, and educational methodologies, this paper provides a comprehensive framework for integrating gender models into teacher education, developing critical thinking skills, and promoting gender-sensitive pedagogy. The strategies discussed in this paper aim to equip future teachers with the knowledge and skills necessary to effectively address gender-related issues in the classroom and contribute to the development of a more inclusive society
Keywords: developing thinking; gender models; teacher education